72 Identifying Perinatal and Neonatal Factors Associated with Autism Spectrum Disorder among Preterm Infants Born < 29 Weeks' Gestation. (29th October 2021) - Busque, Andrée-Anne; Jabbour, Elias; Patel, Sharina; Couture, Élise; Garfinkle, Jarred; Khairy, May; Claveau, Martine; Beltempo, Marc
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Preterm infants born <29 weeks' gestational age (GA) are at risk for autism spectrum disorder (ASD), typically diagnosed at age >2 years. Perinatal and neonatal factors, including interventions and morbidities during neonatal intensive care unit admission, may contribute to the risk of ASD among these infants. Objectives: We aimed to assess the incidence of and risk factors for, ASD among preterm infants born < 29 weeks' GA. Design/Methods: <29 weeks' GA admitted 2009-2017 to two tertiary NICUs and followed ≥18 months at the Neonatal Follow-Up Clinic. Primary outcome was ASD defined as a confirmed diagnosis using standardized testing or suspected diagnosis at >18 months of corrected age. Patient data and 18-month developmental outcomes were obtained from the local Canadian Neonatal Follow Up Network database and from chart review. Stepwise logistic regression was used to identify significant perinatal, neonatal, and socio-economic factors associated with ASD. Results: Among 300 eligible infants, 47 (15.7%) developed ASD (Figure 1, Table 1). Mean follow-up duration was 3.9 ± 1.4 years and mean age at diagnosis was 3.7 ± 1.5 years. Male sex (adjusted odds ratio [aOR] 4.63, 95% CI 2.12, 10.10), small for gestational age status (aOR 3.03, 95% CI 1.02, 9.01), maternal age ≥ 35 years at delivery (aOR 2.22, 95% CI 1.08, 4.57), and tobacco use in utero (aOR 5.67, 95% CI 1.86, 17.29) were significantly associated with ASD. Major neonatal morbidities (retinopathy of prematurity, bronchopulmonary dysplasia, necrotizing enterocolitis, late-onset sepsis, severe neurological injury) were not associated with ASD. Among infants with a complete 18-month corrected age developmental assessment and later diagnosed with ASD, 46% (19/41) did not have significant neurodevelopment impairment (Bayley-III < 70, deafness, blindness, or cerebral palsy). Conclusion: ASD is a significant morbidity among infants born < 29 weeks' GA. ASD was associated with infant and prenatal risk factors but not with neonatal morbidities or socio-economic factors. These findings emphasize the need for ASD evaluation among preterm infants < 29 weeks and for reporting developmental outcomes beyond 18-months corrected age.